TALIS 2018 data indicates that teachers need support for developing skills in Pedagogical Decision Making - Wiksten, Susan (Nordic Journal of Comparative and International Education (NJCIE), 2025)
From a sociology of education perspective, a concern in teacher education is that teaching practices and expectations to the professional role of teachers often build on assumptions that derive from the social context of instruction. Whereas international comparisons regularly focus on characteristics of individuals or selected segments of the population, such as pre-service teachers or individual teacher education programmes, this article contextualizes socially derived expectations using secondary analysis of survey data for fourteen countries across four continents. A review of publicly available data from the World Bank and the Teaching and Learning International Survey (TALIS) was carried out. The secondary analysis consists of a juxtaposition and visualization of descriptive data. Analysis of survey data highlights shared assumptions and expectations across fourteen countries. The data indicates that some teacher attitudes are not a result of characteristics specific to individual teachers or the teacher profession in general but are associated with variation between countries. The article draws theoretically and methodologically on prior Comparative and International Education (CIE) research and proposes that teachers across subject matter specializations and across contexts benefit from the development of Pedagogical Decision-Making skills (PDM). More attention to the development of specific PDM skills is proposed as a means for strengthening teacher resilience.